Febrile children in the Emergency Department: Frequency and predictors of poor outcome. (15th October 2020) - Long, Elliot; Solan, Tom; Stephens, David J.; Schlapbach, Luregn J.; Williams, Amanda; Tse, Wai Chung; Babl, Franz E.
Abstract: Aim: To evaluate the frequency and predictors of poor outcome in febrile children presenting to the Emergency Department. Methods: Retrospective observational study from the Emergency Department of The Royal Children's Hospital, Melbourne, Australia. All children with presenting complaint of fever or triage temperature >38°C over a 6‐month period were included. Poor outcome was defined as: new organ dysfunction or the requirement for organ support therapy (inotrope infusion, mechanical ventilation, renal replacement therapy and extra‐corporeal life support). Predictors evaluated were as follows: initial vital signs, blood tests and clinical scores. Odds ratio, sensitivity, specificity and area under the receiver‐operating characteristics curve were calculated for each predictor variable. Results: Between Jan‐June 2019, 6217 children met inclusion criteria. Twenty‐seven (0.4%) developed new organ dysfunction, 10 (0.2%) required organ support therapy (inotrope infusion in 5, mechanical ventilation in 6, renal replacement therapy in 1, extra‐corporeal life support in 1). Odds of new organ dysfunction, requirement for inotropic support and mechanical ventilation were higher with abnormal initial vital signs, blood tests and clinical scores, though overall test characteristics were poor due to infrequency. Conclusion: Poor outcomes were uncommon among febrile children presenting to the Emergency Department. Vital signs, blood tests and clinical scores were poor predictors.